Lives ‘on hold’ in Europe: an explorative review of literature on youth aspirations and futures in situations of migration and mobility - Kyriaki Doumas; Helen Avery (European Journal of Futures Research, 2024)
Abstract This explorative literature review aims to examine the content and methodologies of recent empirical studies on the aspirations of youth in situations of migration in Europe. The search yielded 30 peer-reviewed social science publications in English for the period 2010–2022, including both intra-European migrants ages 10–24 and youth with backgrounds from outside Europe. Contextual analysis was used to analyse the content of the reviewed studies, while a typology developed by Beckert and Suckert was used to examine features of the future appearing in the studies’ research aims, methodology and findings. The analysis broadly situated the studies within constructivist traditions, occupying a mid-position between deterministic and agency-oriented epistemologies. All the features of the future listed by Beckert and Suckert were found in the material, but the categories 'Temporal configurations of the future' and 'Space of the future' showed greater complexities. Participants in the studies lived in different European countries and the study samples comprised a wide range of ages, socioeconomic backgrounds, and status of residence. Nevertheless, barriers linked to participants' position as migrants were tangible, while the ability these young people had to envisage the future was strongly affected by uncertainties linked to migration policy and administrative decisions on their status. A mismatch could notably be observed between youth aspirations and the opportunities offered by their life situation, which led to delays in life projects and the inability to plan ahead. Critical relevance statement By an analysis of social studies research on aspirations of youth in situations of migration in various European countries, this review highlights the need to consider implications for youth aspirations and life trajectories in both policy and practice Key points • Young people in situations of migration have high aspirations but confront substantial barriers • Uncertainties prevent youth from long-term planning and realising life projects • Current policies create conditions that are not consistent with European values and ambitions